Solve for x
x=20\sqrt{3}+40\approx 74.641016151
x=40-20\sqrt{3}\approx 5.358983849
Graph
Share
Copied to clipboard
10=2x-0.025x^{2}
Use the distributive property to multiply x by 2-0.025x.
2x-0.025x^{2}=10
Swap sides so that all variable terms are on the left hand side.
2x-0.025x^{2}-10=0
Subtract 10 from both sides.
-0.025x^{2}+2x-10=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-2±\sqrt{2^{2}-4\left(-0.025\right)\left(-10\right)}}{2\left(-0.025\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -0.025 for a, 2 for b, and -10 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-2±\sqrt{4-4\left(-0.025\right)\left(-10\right)}}{2\left(-0.025\right)}
Square 2.
x=\frac{-2±\sqrt{4+0.1\left(-10\right)}}{2\left(-0.025\right)}
Multiply -4 times -0.025.
x=\frac{-2±\sqrt{4-1}}{2\left(-0.025\right)}
Multiply 0.1 times -10.
x=\frac{-2±\sqrt{3}}{2\left(-0.025\right)}
Add 4 to -1.
x=\frac{-2±\sqrt{3}}{-0.05}
Multiply 2 times -0.025.
x=\frac{\sqrt{3}-2}{-0.05}
Now solve the equation x=\frac{-2±\sqrt{3}}{-0.05} when ± is plus. Add -2 to \sqrt{3}.
x=40-20\sqrt{3}
Divide -2+\sqrt{3} by -0.05 by multiplying -2+\sqrt{3} by the reciprocal of -0.05.
x=\frac{-\sqrt{3}-2}{-0.05}
Now solve the equation x=\frac{-2±\sqrt{3}}{-0.05} when ± is minus. Subtract \sqrt{3} from -2.
x=20\sqrt{3}+40
Divide -2-\sqrt{3} by -0.05 by multiplying -2-\sqrt{3} by the reciprocal of -0.05.
x=40-20\sqrt{3} x=20\sqrt{3}+40
The equation is now solved.
10=2x-0.025x^{2}
Use the distributive property to multiply x by 2-0.025x.
2x-0.025x^{2}=10
Swap sides so that all variable terms are on the left hand side.
-0.025x^{2}+2x=10
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-0.025x^{2}+2x}{-0.025}=\frac{10}{-0.025}
Multiply both sides by -40.
x^{2}+\frac{2}{-0.025}x=\frac{10}{-0.025}
Dividing by -0.025 undoes the multiplication by -0.025.
x^{2}-80x=\frac{10}{-0.025}
Divide 2 by -0.025 by multiplying 2 by the reciprocal of -0.025.
x^{2}-80x=-400
Divide 10 by -0.025 by multiplying 10 by the reciprocal of -0.025.
x^{2}-80x+\left(-40\right)^{2}=-400+\left(-40\right)^{2}
Divide -80, the coefficient of the x term, by 2 to get -40. Then add the square of -40 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-80x+1600=-400+1600
Square -40.
x^{2}-80x+1600=1200
Add -400 to 1600.
\left(x-40\right)^{2}=1200
Factor x^{2}-80x+1600. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-40\right)^{2}}=\sqrt{1200}
Take the square root of both sides of the equation.
x-40=20\sqrt{3} x-40=-20\sqrt{3}
Simplify.
x=20\sqrt{3}+40 x=40-20\sqrt{3}
Add 40 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}